ANALISIS PENGETAHUAN KEWIRAUSAHAAN DAN JIWA WIRAUSAHA PADA SISWA SMA NEGERI 2 MALANG - Eka Aprilia Hani; Lisa Rokhmani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
This research departs from the problem of lack of understanding of the importance of entrepreneurship in high school. The existence of entrepreneurship subjects is expected to develop students' skills in developing the business and foster the entrepreneurial spirit that is in the students themselves. The type of this research is qualitative descriptive located in SMA Negeri 2 Malang. Technique of collecting data is done through observation, test, interview and documentation. The results showed that students can understand entrepreneurial knowledge well with the thought to open a business and mengmebangkan effort. In addition each student has the characteristics of entrepreneurial spirit that is different in him. The entrepreneurial spirit within the students is committed to work, dare to take risks, look for opportunities and creativity and innovate. DOI: https://dx.doi.org/10.17977/UM014v11i12018p0020